(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Leaf anatomical features of Campanula glomerata L. in different existence conditions were studied. The study has shown that the growth conditions have influenced leaf quantitative anatomical characteristics. A higher number of correlations of morphological and anatomical leaf features is observed under more arid conditions within the species distribution; thickness of palisade mesophyll, palisade coefficient, size and area of stomata of abaxial epidermis, m/S і m2/S ratios are increased, leaf width and stomata number are reduced.